Characterisation of Nox4 Inhibitors from Edible Plants - Kofler, Philipp A.; Pircher, Haymo; von Grafenstein, Susanne; Diener, Thomas; Höll, Monika; Liedl, Klaus R.; Siems, Karsten; Jansen-Dürr, Pidder (Planta Medica, 2013)
NADPH oxidases transport electrons from cytosolic NADPH through biological membranes to generate reactive oxygen species. NADPH oxidase 4, broadly expressed in humans, is an interesting pharmacological target, since its activity is deregulated in several diseases, including pulmonary fibrosis, diabetic nephropathy, and cardiac hypertrophy. Whereas several candidate NADPH oxidase 4 inhibitors were recently described, most of these compounds are either unspecific or toxic. Here we set out to identify new NADPH oxidase 4 inhibitors from edible plants, in an attempt to decrease the number of hits with toxic side effects. We screened a compound library prepared from edible plants for new bioactives with the ability to inhibit the activity of NADPH oxidase 4. Using both cell-based and cell-free assays, we identified several compounds with significant inhibitory activity towards NADPH oxidase 4. For selected compounds, the activity profile towards NADPH oxidase 2 and NADPH oxidase 5 was established, and controls were carried out to exclude general reactive oxygen species scavengers. A number of promising NADPH oxidase 4 inhibitors from edible plants was identified and characterised. Several new chemical entities are disclosed which act as NADPH oxidase 4 inhibitors, and the efficacies of our best hits, in particular several diarylheptanoids and lignans, are comparable to the best available pharmacological NADPH oxidase 4 inhibitors. These findings will provide valuable tools to study mechanisms of NADPH oxidase inhibition.
Keywords: NADPH oxidase 4; Nox4; ROS; inhibitors; dehydrogenase domain; broken cell assay